About tectonic zoning and features of the structure of Russian part of Arctic mobile belt - V. B. Karaulov (Известия высших учебных заведений: Геология и разведка, 2017)
The principles of the tectonic zoning of the continents are discussed. The tectonic zoning of the Russian sector of Arctic mobile belt is considered and a brief characteristic of the West-Arctic and East-Arctic recent platforms, formed at the place of this belt, is given. The data about the position of the boundaries of the recent platforms, about the structure of their basement and sedimentary. The possible approaches to the determination of the structure and tectonic nature of the «transient» complex of the plates of the recent platforms.